Pendampingan Kurikulum Ramah Lingkungan Berbasis Ekoteologi di Pesantren - Firdahus , M. Surgo; Cahyo , Dwi Irfan; rahmawati , Fatya nia (LPPM Universitas PGRI Argopuro Jember, 2026)
This community service program aims to assist Pesantren Darul Istiqomah Kepohbaru in developing an eco-friendly curriculum based on ecotheology as an effort to support sustainable education. Islamic boarding schools have significant potential through their spiritual values, mutual cooperation culture, and environmental assets that can be integrated into ecological learning. The method used is Asset-Based Community Development (ABCD), which includes the stages of inculturation, discovery, design, define, and reflection involving caregivers, teachers, and senior students. The activities were conducted through intensive workshops that provided participants with an understanding of ecotheology concepts and the preparation of environmentally friendly lesson plans. The results show an increase in ecological awareness among the pesantren community and the development of a draft ecotheology-based curriculum that integrates environmental values into learning and students’ daily activities. This program demonstrates that the ABCD approach is effective in optimizing local assets and strengthening an environmentally conscious pesantren culture oriented toward sustainable education aligned with Islamic values.